2020
DOI: 10.1038/s41598-020-63036-1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical clustering of MS/MS spectra from the firefly metabolome identifies new lucibufagin compounds

Abstract: Metabolite identification is the greatest challenge when analysing metabolomics data, as only a small proportion of metabolite reference standards exist. clustering MS/MS spectra is a common method to identify similar compounds, however interrogation of underlying signature fragmentation patterns within clusters can be problematic. Previously published high-resolution LC-MS/MS data from the bioluminescent beetle (Photinus pyralis) provided an opportunity to mine new specialized metabolites in the lucibufagin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(51 reference statements)
0
16
0
Order By: Relevance
“… 27 In addition, we employed the recently described BioDendro workflow, which enables hierarchical clustering of MS 2 spectra and presents the results as a tree. 28 After molecular networking, background and media subtraction, a total of 6260 compounds were detected ( Figure 2 A,B). The majority of these molecules were detected under all three culturing conditions, though distinct sets of metabolites were also found in each extract, with the OBA extract containing the highest number of unique metabolites ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 In addition, we employed the recently described BioDendro workflow, which enables hierarchical clustering of MS 2 spectra and presents the results as a tree. 28 After molecular networking, background and media subtraction, a total of 6260 compounds were detected ( Figure 2 A,B). The majority of these molecules were detected under all three culturing conditions, though distinct sets of metabolites were also found in each extract, with the OBA extract containing the highest number of unique metabolites ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…28 FBMN allows for the discrimination of isomers and quantitative interpretation of the molecular network, while BioDendro uses dynamic binning and hierarchical clustering of MS 2 spectra and can function as a complementary analysis to molecular networking. 27,28 Metabolites were annotated by matching the observed MS 2 spectra with reference spectra in the GNPS libraries 29 or using Network Annotation Propagation (NAP), 30 SIRIUS, 31 Met-Work, 32 or Competitive Fragmentation Modeling for Metabolite Identification 3.0 (CFM-ID 3.0). 33 ■ RESULTS AND DISCUSSION Genomic Analysis of Specialized Metabolite Biosynthetic Gene Clusters in S. scabiei.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The developments in metabolomics platforms enable large-scale MS/MS experiments containing thousands of distinct spectra from a single sample. These detected features and their MS/MS spectra can be used for matching to spectral libraries and can include indicative fragmentation patterns that provide information on the often yet unknown chemical structures that were fragmented [221,222]. However, this process is still cumbersome and laborious for large-scale data, particularly for plant metabolomics data which is vastly diverse in physiochemical properties [222,223].…”
Section: Large-scale Metabolite Annotationmentioning
confidence: 99%
“…These detected features and their MS/MS spectra can be used for matching to spectral libraries and can include indicative fragmentation patterns that provide information on the often yet unknown chemical structures that were fragmented [221,222]. However, this process is still cumbersome and laborious for large-scale data, particularly for plant metabolomics data which is vastly diverse in physiochemical properties [222,223]. Hence, we are currently witnessing the development of tools that can analyze such large-scale, complex metabolomic data using computational networking approaches such as molecular networking (MN), which provides visualization of all the detected features and their chemical relationships by grouping structurally similar features into a network to enable mining of the metabolome (Figure 4) [224][225][226].…”
Section: Large-scale Metabolite Annotationmentioning
confidence: 99%
“…We use these molecular fingerprints to calculate pairwise distances between chemical features and hierarchically cluster the fingerprint vectors to generate a tree representing their chemical structural relationships. Although alternative approaches to hierarchically cluster features based on cosine similarity of fragmentation spectra exist [19][20][21] , we use molecular fingerprints predicted by CSI:FingerID for this. Previous work has shown that CSI:FingerID outperforms other tools for automatic in silico structural annotation 22 .…”
mentioning
confidence: 99%